2017
DOI: 10.1002/cjas.1429
|View full text |Cite
|
Sign up to set email alerts
|

The effect of error orientation, motivation to learn, and social support on training transfer intentions: A moderated mediation model

Abstract: This study aims to assess whether trainees’ errors orientation can influence their motivation to learn and their intention to transfer training. Data were collected from 275 trainees participating in a corporate training program offered by a Canadian government agency. Results show that the concept of learning by error positively influences trainees’ levels of motivation and their intention to transfer learning. Results also confirm the mediating role of motivation between the concept of learning by error and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The influence of learner readiness on transfer was established through our data to depend on the presence (or absence) of supervisor support, thus supporting H3. This is in line with Lauzier and Mercier (2017), who have confirmed moderation by supervisor support in a mediated relation. Extant literature on transfer cites self-efficacy and transfer climate (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The influence of learner readiness on transfer was established through our data to depend on the presence (or absence) of supervisor support, thus supporting H3. This is in line with Lauzier and Mercier (2017), who have confirmed moderation by supervisor support in a mediated relation. Extant literature on transfer cites self-efficacy and transfer climate (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Motivation as another trainee characteristic before training positively influences transfer (Lauzier and Mercier, 2017). Learning transfer is more when trainees have the confidence to retain new KSAs and are also motivated to apply new KSAs.…”
Section: Rationale Behind the Choice Of Variablesmentioning
confidence: 99%
“…In addition, our findings align with the literature on knowledge flows and learning experiences in organizations more generally. This research demonstrated that positive and trusting relationships at work are of paramount importance for the extent to which employees are able and willing to exchange information and knowledge (Burmeister et al, 2018; Hsu & Chang, 2014; Nifadkar et al, 2019; Sias, 2005) and engage in learning at work (Blume et al, 2010; Lauzier & Mercier, 2018; Massenberg et al, 2015). Our research demonstrates that coworker contact quality creates a relational work context in which employees can engage in daily knowledge seeking without facing the detrimental consequences of being overloaded.…”
Section: Discussionmentioning
confidence: 90%
“…motivation), but may only perform the action if there is also a deliberate intention or plan to behave in a certain way or under specific circumstances. Research on intention to transfer has not been examined much in terms of direct transfer outcomes, but rather research has examined individual attributes that can predict intentions (Gegenfurtner, 2013; Hutchins et al , 2013; Lauzier and Mercier, 2017). For example, research has found that attitudes toward training content and motivation positively affect intention to transfer immediately after training (Gegenfurtner, 2013; Lauzier and Mercier, 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%